Ovarian Cancer During Pregnancy: A Case Report and Literature Review - Hummeida, Moawia E. (Clin Pract, 2015)
Ovarian cancer during pregnancy is a rare event. Little is known about the treatment of this condition due to lack of prospective randomized trials and cohort studies. In this paper the authors reported a rare case of small cells ovarian cancer, diagnosed at 16 weeks of gestation, treated with conservative surgery at 18 weeks and chemotherapy. At week 38, the patient underwent caesarean section and delivered a healthy baby girl. Staging surgery was then carried out followed by adjuvant chemotherapy. Thus the findings from this case concluded that prognosis and quality of the patient’s life should be a priority, chemotherapy during the second trimester seems to be safe however, potential risks of this interventions still has to be considered.